Еволюція управлінської ролі декана в умовах трансформації сучасного ЗВО - Кувачов, Володимир Петрович; Kuvachov, Volodymyr (Запоріжжя : ТДАТУ, 2026)
UA: У статті розглянуто трансформацію функцій декана факультету в умовах розвитку сучасної системи вищої освіти. Обґрунтовано зростання значення менеджерських компетентностей у діяльності декана поряд із традиційним академічним лідерством. Показано, що ефективність розвитку факультету значною мірою визначається здатністю керівника поєднувати науково-педагогічний досвід із інструментами стратегічного управління. /// EN: The article examines the transformation of the functions of the dean of the faculty in the context of the development of the modern system of higher education. The growing importance of managerial competencies in the activities of the dean is substantiated, along with traditional academic leadership. It is shown that the effectiveness of the development of the faculty is largely determined by the ability of the head to combine scientific and pedagogical experience with strategic management tools.
The evolution of the dean’s managerial role in the context of the transformation of a modern higher education institution
Keywords: декан факультету; управління закладом вищої освіти; академічне лідерство; менеджмент освіти; стратегічний розвиток; dean of the faculty; management of a higher education institution; academic leadership; educational management; strategic development